Abstract of Keynote Speaker : Potential of e-Learning for Enhancing Graduate and Undergraduate Education - Usagawa, Tsuyoshi; Ogata, Kohichi (IPTEK Journal of Proceedings Series, 2015)
Many educational institutes as well as governments focus on education utilize Information Communication Technology (ICT), and the word â€œe- Learningâ€ is used in various contexts. There are many attractive aspects in e-Learning such as possibility to reduce the restriction due to spatial and temporal distance, possibility to improve the quality of education, and possibility to share educational resources among institutions. It is obvious to reduce the restriction by means of ICT such as mobile network. Also when a course is designed, the achievement level needs to be defined to satisfy the expected level of curriculum such as the diploma policy. In such a design process, it is possible to improve and sustain the achievement level of the course. In this paper, the principle motivation to utilize campus-wide e- Learning in Kumamoto University is explained as the background, then example courses of undergraduate and graduate programs are detailed to discuss the potential of e- Learning for enhancing education